Main aspects of renewable energy integration - Chobanov, Veselin; Pasarelski, Rosen (Yearbook Telecommunications, 2024)
The transition in the energy sector is essential for reducing carbon emissions and building a sustainable future. In this process, wind and solar energy play a leading role, offering environmentally friendly solutions. Their effective integration into the power system requires addressing various technical, operational, and regulatory challenges. This study examines long-term strategies for power system planning, which are crucial for maintaining the security of electricity supply. The analysis presents energy transition scenarios applied in Europe, clarifying their significance and timeline for implementation. This review provides an overview of existing studies on the technical, regulatory, and climatic aspects of renewable energy integration, highlighting key findings to support stakeholders in risk assessment and decision-making within the current decarbonization framework.